Influence of the key-hole on fatigue life in friction stir linear welded aluminum to magnesium. (December 2017) - Rao, H.M.; Jordon, J.B.; Boorgu, S.K.; Kang, H.; Yuan, W.; Su, X.
Highlights: Key-hole has no direct role in initiating or propagating the fatigue crack. Lower fatigue life predominantly due to reduction in the overall weld length. Weld length is controlling parameter in evaluating fatigue strength. Abstract: The retrieval of the weld tool at the end of the friction stir welding process leaves behind a distinctive physical feature in the welded material which is commonly referred to as the exit-hole or the key-hole. Conventionally, the key-hole is left intact in the weldment due to the complexity involved in the design and manufacturing process, which then becomes an integral part of the weldment. To study the influence of the key-hole on fatigue life, rolled aluminum 6022-T4 sheet was friction stir linear welded to die-cast magnesium AM60 B sheet in lap-shear configuration. The lap-shear weld coupons with the key-hole were fatigue tested at different load levels at load ratio of R = 0.1. A significant reduction in fatigue life was observed as compared to friction stir linear welded lap-shear coupons without the key-hole. Two distinctive failure modes were observed; (a) at maximum fatigue loads at and above 1500 N, the welds failed due to interfacial failure through the weld nugget and, (b) at maximum fatigue loads below 1500 N, the welds failed due to kinked crack growth through the top aluminum sheet. Nevertheless, analysis of the fatigue results suggests that the key-hole had no role in initiating or propagating the fatigue crack. But the reduction in linear weld length due to the presence of the key-hole in the lap-shear test coupons combined with the existence of the brittle inter metallic compounds in the weld nugget contributed to lower fatigue life as compared to lap-shear welds produced without the key-hole. To further confirm the failure analysis in this study, fatigue predictions were made using a structural stress approach for the welds with and without the key-hole. The structural stress calculations show that the experimental fatigue results can be correlated to the reduction in weld length due to the key-hole.